Like a bird on the wire - "Bhardwaj, Chhavi" (New Delhi, 2018)
Nethra Kaul is sharp, efficient, beautiful and single. A quintessential ?good girl?, she believes in doing the ?right thing?, always. Only, her life isn?t all that right. A broken heart? Check. Misfit at work? Double-check. Hopeless romanticism? Not enough checks in the world! Avinash Rathore, her batchmate from the IAS, is the man she had loved and wanted, very much. Avinash is a high-flyer and his life looks picture perfect at the moment ? a soaring career, a lovely wife and a beautiful child. What more could he possibly want? What more, other than the intense, sublime love that had once blossomed in the salubrious environs of Mussoorie, where Nethra and Avinash had trained as probationers? The tentacles of fate are closing in fast as Nethra and Avinash come together, one more time, for something that will prove to be as disastrous as it is enticing. How will Avinash get trapped in a labyrinth spawned out of animosity? Does a woman need a man in her life to feel complete? Will Nethra find solace, will she find love?
Keywords: Fiction